2009
DOI: 10.2165/00023210-200923030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness as a Predictor of Response to Cholinesterase Inhibitors in Alzheimerʼs Disease

Abstract: Although the magnitude of effect was moderate, carotid IMT could be a significant predictor of clinical response to cholinesterase inhibitors in patients with Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…IMT-dependent regional cerebral blood flow (rCBF) differences have been identified 42 , and neuronal viability suffers with presence of subclinical atherosclerosis 43 . Carotid IMT has also been increasingly linked with future dementia, both due to Alzheimer’s disease and vascular causes 13, 44, 45 , and IMT has been shown to predict response to cholinesterase inhibitors in Alzheimer’s disease 46 . While there is no shortage of explanatory hypotheses, the specific interrelations and pathways are yet to be understood, especially in relation to demographic subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…IMT-dependent regional cerebral blood flow (rCBF) differences have been identified 42 , and neuronal viability suffers with presence of subclinical atherosclerosis 43 . Carotid IMT has also been increasingly linked with future dementia, both due to Alzheimer’s disease and vascular causes 13, 44, 45 , and IMT has been shown to predict response to cholinesterase inhibitors in Alzheimer’s disease 46 . While there is no shortage of explanatory hypotheses, the specific interrelations and pathways are yet to be understood, especially in relation to demographic subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal values of IMT also significantly increase the risk of conversion from amnestic MCI to AD (Viticchi et al, 2012). In a longitudinal study involving a 6-month galantamine treatment of AD, the patients with lower values of IMT at baseline had better response to treatment (Modrego et al, 2009), which suggests that AD patients with lower cerebrovascular burden have slower progression of disease. Details of ultrasound projects focused on IMT and carotid atherosclerosis in AD are listed in Table 1.…”
Section: Extracranial Ultrasound In Admentioning
confidence: 99%
“…Modrego and colleagues [1] write: ''IMT is widely recognized as a good marker of atherosclerosis in general and could be a useful surrogate marker of cerebrovascular burden in the brain of patients with Alzheimer's disease y''. It has to be specified that the consensus as to whether to consider increased C-IMT as a marker of subclinical atherosclerosis is still contingent within the scientific community and subject to debate.…”
Section: C-imt As a Surrogate Marker For Atherosclerosismentioning
confidence: 99%
“…Modrego and colleagues [1] write: ''A 12-year study of a population-based cohort of 91 elderly women showed that an increased IMT of the carotid bifurcation was an independent predictor of poor memory and reduced cognitive speed. [7] Likewise, in a cohort of 400 men, increased IMT of the carotid artery was associated with poorer performance on memory tests.…”
Section: C-imt As a Surrogate Marker For Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation